Ant architecture : the wonder, beauty, and science of underground nests - Tschinkel, Walter R. (Walter Reinhart), 1940- (Princeton University Press, 2021)
"Many animals, from birds to insects, build structures using wood, soil, or a range other materials. Surprisingly to most people, a similarly diverse array of animal homes exist underground, in the hidden world beneath our feet. This is particularly true for ants who excavate large and complex nests in which they shelter, reproduce and generally go about their lives. Despite the existence of this vast underground world, it has remained largely unexplored. Walter Tschinkel, however, has spent his career researching underground ant nests in his home state of Florida (where they are particularly prevalent) and this book is his story of discovery about what he has learned about these nests and they reveal about ant biology and behavior more broadly. Tschinkel starts the book by describing just how he studies ants nest - an arduous excavation process which involves first filling the nests with plaster, molten metal or wax. But this is a book driven by fascinating questions and the experiments the author has devised to try and answer them. How does nest architecture vary across ant species? How are new nests excavated during colony relocation? Are the ants organized within the nest? Do ants have "architectural plans?" What is the effect of all this nest excavation on soils? And how does the division of labor within the nest work? Ultimately, Tschinkel provides answers to many of these questions, but also acknowledges what mysteries, including why nests evolved in the first place, still remain. In telling this story, Tschinkel introduces readers to the surprising beauty and architectural complexity of underground ant nests and to how scientific research on them is done"--